Key historical events in Gedeo from the Italian Period to the Michelle Peasant Uprising (1935-1960) - Legesse Gemeda, Girma; Tesema Ta'a (HISTORICAL: Journal of History and Social Sciences, 2025)
Given the various causes, trajectories, and impacts of historical issues, studies should also be multifaceted, with one important component being the reconstruction of local history that sheds light on specific locations and periods, thereby integrating the periphery into the center. Until recently, Ethiopian historiography was characterized by an overemphasis on the northern rulers' and political institutions. The incorporated south, as well as the major themes affecting its peoples, were less treated. This study explores the changes and continuities since Menilek's occupation, focusing on land, the Italian administration, the Plane incident, and the Michele peasant uprising from 1935 to the 1960. I argue that the conquest of the Gedeo of Southern Ethiopia by Menelik's forces in 1895, along with the subsequent domination by northerners, led to a series of socio-political and economic crises in Gedeo. This condition eroded internal cooperation in fighting external forces, allowing Italy to easily control the area, eventually culminating in the Michele peasant uprising of the 1960s. This study revealed that the Gedeo people enjoyed greater freedom during the brief Italian occupation from 1935 to 1941 than they experienced under the long imperial rule. This research also uncovered an airplane incident in the Gedeo zone related to the Italian war, which has not been addressed in any previous studies. After liberation, the Gedeo people faced significant hardships, leading to the Michelle peasant rebellion in the 1960s. The Italian period was brief but had a significant impact, characterized by more changes than continuities in their ruling approach and administration. Drawing on archival sources, including government documents, reports, news articles, and interviews with knowledgeable elders, this study highlights the changes and continuities in Gedeo from a grassroots perspective, challenging the top-down historical narratives that dominate Ethiopian historiography. Regarding the plane incident, since this is the first research on the event, it solely used photographs of the remaining portion of the aircraft, oral informants including eyewitnesses, and group discussion. This study adds to our understanding of local history by documenting the effects of occupation and how residents reacted beyond the sociopolitical repercussions in Gedeo. Unlike some of the previous studies in Ethiopia, this article broadens the geographical scope and thematic areas of Ethiopian history, as it was carried out in a relatively periphery region. It highlights the significance of incorporating local history to successfully address the long-term repercussions of isolation from national and economic activities, rather than adhering to center-periphery paradigms. In General this study mainly employed historical methods to gather key primary and secondary sources on the topic.